Do earnings management and institutional ownership affect stock market liquidity? - Yani Permatasari, Dian Agustia, Bagus Prasetyo, (Opción, 2019)
This study aims to examine the effect of earnings management and institutional ownership on stock market liquidity. Using 963 companies listed in Indonesia Stock Exchange during 2014-2016, this study uses multiple linear regression to test the hypotheses. The results provide empirical evidence that both earnings management and institutional ownership have a negative effect on stock market liquidity. In conclusion, earning management has a significant negative effect on stock market liquidity.